Quality and Safety of Meat Products - Panea, Begoña; Ripoll, Guillermo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Food safety is a major problem around the world, both with regard to human suffering and with respect to economic costs. Scientific advances have increased our knowledge surrounding the nutritional characteristics of foods and their effects on health. This means that a large proportion of consumers are much more conscious with respect to what they eat and their demands for quality food. Food quality is a complex term that includes, in addition to safety, other intrinsic characteristics, such as appearance, color, texture and flavor, and also extrinsic characteristics, such as perception or involvement.